Application of Pocket Book on Rights Protection and Manipulative Thinking Tools of Hanoi Tower for Indonesian Migrant Workers Living and Working in Hong Kong - Riyanto, R Benny; Hidayah, Isti; Irawaty, Irawaty; Pambudi, Bagus Dwi (Universitas Negeri Semarang, 2025)
Indonesian migrant workers (PMI) living and working in Hong Kong have access to a fairly good legal system, but many have not been able to make optimal use of it due to a lack of understanding and limited support. In addition to legal protection rights, PMI have the right to live comfortably and healthily. In addition to strengthening their understanding of their rights and legal protection, a variety of activities are needed to fill their free time, including simple but useful activities to maintain their comfort and well-being. To address this, this community service partnership (PMK) activity provides a solution by utilizing the Pocket Book of Rights and Protection and manipulative thinking and fitness tools. The partner for this PMK program is PCIA (Special Branch Leader of 'Aisyiyah) in Hong Kong, while the target partner is the Domestic Female Migrant Workers in Hong Kong. The activity was held on Sunday-Monday, July 20-21, 2025, at Victoria Park and Ammr Wanchai Mosque in Hong Kong. The results of the activity showed a positive response from the participating PMI members of the PKMK program. A publication of the activity was released in the media, along with a copyright certificate for the Pocket Book on the Rights and Protection of Women PMI in Hong Kong. Meanwhile, the video of the activity is currently in the editing process, and its publication in a service journal is in draft status.